The effect of superstar gig workers on shareholder value: evidence from professional wrestling. Issue 2 (7th September 2020) - Carter, Kelly
Abstract : Purpose: The purpose of this paper is to measure the effect of superstar gig workers, defined as independent contractors who are the most successful in their field, on shareholder value. Gig workers comprise as much as 33% of the workforce and are projected to exceed 50% by 2028. Thus, understanding their impact on shareholder value is important. Design/methodology/approach: This paper uses OLS regression analysis. To establish causality regarding wealth effects, the sudden deaths of superstar gig workers are used. To facilitate the uncontaminated measurement of wealth effects, sudden deaths that coincide with a significant event on a [−3, 3] window about the death event are not used. Findings: The sudden death of a superstar gig worker causes shareholder wealth to increase significantly by 0.35% or almost $1.5m. Rational and behavioral explanations are offered for this result. Research limitations/implications: Generalizability is limited because data on superstar gig workers in traditional corporations are unavailable. For this reason, this paper uses the only available data, namely, data on superstar wrestlers, who are contracted to perform in matches (i.e. "gigs") in a lucrative promotion (e.g. World Wrestling Entertainment (WWE)). Future research could examine the effect of corporate gig workers on shareholder value if the data become available at some point. Originality/value: This paper is the first to document the effects of any type of gig worker, whether superstar or regular, on shareholder value.